f ( x ) = e x ⋅ sin x
For non-zero values of f ( x ) , simplify the expression below. lo g 2 f ( x ) f ( 2 0 1 6 ) ( x )
Notation : f ( n ) ( x ) denotes the n th derivative of f ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I took out the general Derivative :
f n ( x ) = 2 n / 2 ⋅ e x ⋅ sin ( x + 4 n π )
f ( x ) f ( 1 ) ( x ) f ( 2 ) ( x ) f ( 3 ) ( x ) . . . ⟹ f ( 2 0 1 6 ) ( x ) ⟹ lo g 2 f ( x ) f ( 2 0 1 6 ) ( x ) = e x sin x = 2 i ( e ( 1 − i ) x − e ( 1 + i ) x ) = 2 i ( ( 1 − i ) e ( 1 − i ) x − ( 1 + i ) e ( 1 + i ) x ) = 2 i ( ( 1 − i ) 2 e ( 1 − i ) x − ( 1 + i ) 2 e ( 1 + i ) x ) = 2 i ( ( 1 − i ) 3 e ( 1 − i ) x − ( 1 + i ) 3 e ( 1 + i ) x ) = . . . = 2 i ( ( 1 − i ) 2 0 1 6 e ( 1 − i ) x − ( 1 + i ) 2 0 1 6 e ( 1 + i ) x ) = 2 i ( ( − 2 i ) 1 0 0 8 e ( 1 − i ) x − ( 2 i ) 1 0 0 8 e ( 1 + i ) x ) = 2 i ( ( − 2 ) 1 0 0 8 e ( 1 − i ) x − ( 2 ) 1 0 0 8 e ( 1 + i ) x ) = 2 1 0 0 8 ⋅ 2 i ( e ( 1 − i ) x − e ( 1 + i ) x ) = 2 1 0 0 8 e x sin x = 1 0 0 8 As ( 1 − i ) 2 = − 2 i , ( 1 + i ) 2 = 2 i And i 4 = 1
Amazing way to solve
Log in to reply
Glad that you like the solution. Upvote if you have not.
By taking the first few derivatives of f ( x ) = e x sin x , it can be observed that f ( 4 n ) ( x ) = { − 2 2 n f ( x ) if 4 n ≡ 4 (mod 8) 2 2 n f ( x ) if 4 n ≡ 8 (mod 8)
Since 8 divides 2 0 1 6 , f ( 2 0 1 6 ) ( x ) = f ( 4 × 5 0 4 ) ( x ) = 2 1 0 0 8 f ( x )
lo g 2 ( f ( x ) f ( 2 0 1 6 ) ( x ) ) = lo g 2 ( f ( x ) 2 1 0 0 8 f ( x ) ) = lo g 2 ( 2 1 0 0 8 ) = 1 0 0 8
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = e x ⋅ sin x
We can use the product rule of differentiation with g ( x ) = e x and h ( x ) = sin x respectively.
Thus, f ′ ( x ) = g ′ ( x ) ⋅ h ( x ) + h ′ ( x ) ⋅ g ( x ) = e x ⋅ sin x + cos x ⋅ e x = e x ⋅ ( sin x + cos x )
Using the same method, we can proceed with the second degree differentiation:
f ′ ′ ( x ) = e x ⋅ ( sin x + cos x ) + ( cos x − sin x ) ⋅ e x = e x ⋅ ( 2 cos x ) = 2 e x ⋅ cos x
With the factor 2 coefficient, the differentiation can continue with the factor remained:
f ′ ′ ′ ( x ) = 2 e x ⋅ cos x + 2 e x ⋅ ( − sin x ) = 2 e x ⋅ ( cos x − sin x )
Finally, we can evaluate the fourth degree of differentiation:
f ( 4 ) ( x ) = 2 e x ⋅ ( cos x − sin x ) + 2 e x ⋅ ( − sin x − cos x ) = 2 e x ⋅ ( − 2 sin x ) = − 4 e x ⋅ ( sin x )
As we can see, the function f ( 4 ) ( x ) = − 4 ⋅ f ( x ) . In other words, by differentiation for 4 times, such derivative can be evaluated by multiplying the original function f by a factor of − 4 .
Now if we differentiating for 2 0 1 6 times as stated in the question, the desired derivative can be calculated as shown:
f ( 2 0 1 6 ) = ( − 4 ) 4 2 0 1 6 ⋅ f ( x ) = 4 5 0 4 ⋅ f ( x ) = 2 1 0 0 8 ⋅ f ( x ) .
Therefore, lo g 2 f ( x ) f ( 2 0 1 6 ) ( x ) = lo g 2 2 1 0 0 8 = 1 0 0 8